Ethnocultural Approach to the Formation of Musical and Pedagogical Repertoire on the Example of Vocal Lyrics of Chuvash Composers - Alisa L. Agakova (Publishing house "Sreda", 2022)
The purpose of the article is to substantiate the ethno-cultural approach to the formation of the musical and pedagogical repertoire of students of the Chuvash State Institute of Culture and Arts. The implementation of the ethno-cultural approach ensures the orientation of their professional training to the development of culture as a historically determined type of human activity with certain ethnic characteristics. The author examines the potential of Chuvash vocal lyrics in the aspect of an ethnocultural approach, for which he analyzes romance in detail as a genre of Chuvash composer music. Based on the method of stylistic analysis, conclusions are drawn about the derivative character of the Chuvash romance, which goes back through the Russian medium to the medieval European musical tradition. The first Chuvash romances were vocal works based on the words of the classics of Russian literature A. Pushkin and M. Lermontov translated into the Chuvash language. Subsequently, independent Chuvash works with an ethnic sound appeared in the Chuvash musical art (works by O. Agakova, Y. Grigoriev). Romances have enriched Chuvash chamber music with vivid artistic images, they are characterized by a deep insight into the drama of verse, sincerity, lyricism and nobility of utterance, a variety of forms. The musical and pedagogical repertoire of vocal students should be supplemented with works of both the early stage (romances to the words of Pushkin and Lermontov translated into Chuvash) and modern (romances with ethnic sounding accompaniment with a characteristic Chuvash folk music mode and metrorhythmics, with Russian and Chuvash texts).